Itō Toyō et la question de « l’agir technique et social » - Xavier Guillot (Projets de Paysage)
In recent decades Japan has experienced major economic, social and environmental events. As evidence of the fragility and vulnerability of this country it has undergone a bursting of a real estate bubble, demographic decline, and two earthquakes, one in Kōbe and the other in Tōhoku. It is in this context that the career path of the architect Itō Toyō underwent a remarkable change which was set off by a challenge to prevalent modern thinking in the practise of spatial design projects. Two actions carried out in the Tōhoku region and in the Seto Inland Sea which bear witness to this are analyzed in this article: one concerns the construction of a community house, the other concerns the regeneration of an island community: Omishima. These actions illustrate a singular "social and technical approach" in project management: one based on the sharing of skills with the inhabitants and local actors in the design process, and the other resorting to an economy of means in the implementation of the project. It is also an approach that questions the boundaries of knowledge in the disciplines of spatial and project design and proposes to extend beyond their scope.